If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v = (50 + -2x)(50 + -2x)(x) Reorder the terms for easier multiplication: v = x(50 + -2x)(50 + -2x) Multiply (50 + -2x) * (50 + -2x) v = x(50(50 + -2x) + -2x * (50 + -2x)) v = x((50 * 50 + -2x * 50) + -2x * (50 + -2x)) v = x((2500 + -100x) + -2x * (50 + -2x)) v = x(2500 + -100x + (50 * -2x + -2x * -2x)) v = x(2500 + -100x + (-100x + 4x2)) Combine like terms: -100x + -100x = -200x v = x(2500 + -200x + 4x2) v = (2500 * x + -200x * x + 4x2 * x) v = (2500x + -200x2 + 4x3) Solving v = 2500x + -200x2 + 4x3 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Simplifying v = 2500x + -200x2 + 4x3
| y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= | | (4z+7)(5+z)=0 | | 1.2=-1.4+20x | | -9x+4y=7 | | 5x-y=14.9 | | 5x+7=-6+2x+19 | | 4x+y-4=0 | | 4x-9=-3x+5 | | 3(4x-2)+5x=30x | | S^2+2s= | | -4x-9=2x+9 | | 2=2.2x-15 | | 5-11p=17 | | 18x-12y+23=0 | | 8.5+3(9-5)= | | -4(7)-2y=-10 | | 3x+(-5x)= | | 55(6x-6)(7x+1)= | | -10x-10(-10)=20 | | y^2+4x+10y+29=0 | | 2e-3=7e-8 | | 6-3(3x-5)=8x-98 | | -0.7(4y-3)+2.3y=-0.3y+2.1 | | 8k-7=11-2k | | 7y-5x=29 | | 2(3x+2)-3=x-39 | | 35+146-1=180 | | 4y-18=3(2y-4) |